Impact of Forest Cover Change on Available Water Resources: Long-Term Forest Cover Dynamics of the Semi-Arid Dhofar Cloud Forest, Oman - Arnold, Romy; Haug, Jan-Karl; Lange, Maximilian; Friesen, Jan (Frontiers in Earth Science, 2020)
Forest cover dynamics are an important indicator for climate change as well as for land conversion studies. Based on an analysis of 30 years of Landsat data a forest cover time series was generated and analyzed for the Dhofar mountains in Oman. The Dhofar mountains in Southern Oman with its semi-arid cloud forest is an important asset for livestock, water resources, and tourism. In this study we investigated whether forest cover trends are distinguishable and what impact forest cover changes have on water availability. To cope with gaps in the Landsat dataset the Dhofar mountains were divided into regions of interest (ROIs) that were based on hydrologic catchment boundaries. The results show, that, despite increasing pressure from tourism and increasing livestock numbers, the forest cover shows slight but not significant increases in most ROIs and significant forest cover increases in three ROIs. Overall, forest cover during the past 30 years is at least stable and most probably slightly increasing. With regard to water resources results show that, the impact of cloud forest interception amounts to an additional subcanopy water input of about 15 to 150 % of annual rainfall. This additional water is only available below tree cover. Part of that water is, of course used by plant transpiration, however, the stemflow portion which is exceptionally high in this region infiltrates directly into deeper soil layers and eventually leads to groundwater recharge.